Three-Layer Problem on Heat Exchange in a Medium with Counterflows - Filippov, A. I. (Journal of engineering physics and thermophysics, 2024)
With the use of the asymptotic method, it is shown that the three-layer problem on the conjugate heat exchange in an anisotropic medium with counterflows of liquid, formulated in the zero approximation, is equivalent to the analogous problem formulated using the Newton law. It was established that in the case where the counterflows of liquid in such a medium have equal strengths, the summary convective heat transfer in the medium is suppressed, and the medium takes new properties consisting in the appearance of heat flow mixed in nature, whose value is determined by the relation similar to the Fourier heat conduction law. By this meant that in the case where a temperature gradient is superimposed on a three-layer system of equivalent counterflows of liquid, in it there arises a heat flow having a value proportional to the temperature gradient in the medium and propagating in the direction opposite to the direction of this gradient. The effective coefficient of heat conductivity of medium, generated in it by the counterflows of liquid, separated by an immovable layer, is proportional to the square of the velocity of these flows. An immovable layer in a medium, separating the counterflows of liquid, increases the generation of heat in the medium, and the heat flow generated exceeds substantially the molecular one even in the case where it has a low velocity. Such processes provide the mass exchange in living organisms and their heat exchange with the environment.